(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Internet is a huge resource of information, but only the small portion of it is visible to regular users. More than 90 per cent of the web is hidden and to be able to see it, users need to use specific software like Tor. Currently there are more than 2.5 million daily users using Tor to surf the “hidden web”. Ever since Bitcoin and other virtual currencies became popular, more and more users started using Tor for illegal activities. These activities include exchanging illegal goods such as drugs, weapons, illegal data, and stolen credit cards information. The aim of this paper is to analyse the content of anonymous marketplace in one short period of time (72 hours) according to different products offered, scale of performed transactions, origin of the seller, and customer evaluation of the seller. For the needs of this paper, specialised crawling software was developed and as a result, 35 gigabytes of data was downloaded from one of the many black markets used by Tor users. The study shows that in that period, more than 5000 different products worth 1.8 million dollars were listed on the market. The research includes 2500 transactions each worth on average 51 dollars. With the advances in the technology and a growing number of Internet users, further growth of illegal activities on the “dark web” can be expected. It is interesting to analyse how the transactions are closed on the “dark web” since there are no legal institutions or any legal frame for business. These transactions are based on trust, confidence and customer evaluation on social networks. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.